STUDI PAKAN KAKAKTUA TANIMBAR (Cacatua Goffiniana) DI DESA LORULUN, KECAMATAN WERTAMRIAN, KABUPATEN KEPULAUAN TANIMBAR - Daylangi, Tegar Aulia Fadly; Pattinasarany, Cornelis Katje; Tuhumury , Andri (PT. BARRINGTONIA ASIATICA LESTARI, 2024)
This study aims to analyze the feed of Tanimbar cockatoos (Cacatua goffiniana) in Lorulun Village, Wertamin District, Tanimbar Islands Regency. In this study, the method of data collection was by field observation. The data collected included vegetation analysis data and identification of types of feed for Tanimbar cockatoos (C. goffiniana). The results of the analysis conducted in Lorulun Village, Wertamrian District, Tanimbar Islands Regency can be concluded that there are 10 types of plants that are natural food for Tanimbar Cockatoos at the research location and the most favored or liked by these birds are Bintaro Plants (Cerbera manghas), Teak (Tectona grandis), Rambusa (Passiflora foetida), Petai Cina (Leucaena leucocephala), Canary (Canarium ovatum) and several agricultural crops (Corn, Papaya, Coconut, Cassava. The part of the plant that is used as food and most consumed by Cockatoos is the fruit compared to the leaves and skin. Overall, the three blocks showed a fairly good availability of food, with variations in the dominance of plant types that can support the survival of Tanimbar Cockatoos (C. goffiniana). As a result of this deficiency, Tanimbar cockatoos (C. goffiniana) look for food in agricultural land, resulting in conflict with humans and damage to cultivated plants.